Layered silicate magadiite–derived three-dimensional honeycomb-like cobalt–nickel silicates as excellent cathode for hybrid supercapacitors. (December 2021) - Jing, X.; Zhang, Y.; Dong, X.; Mu, Y.; Liu, X.; Meng, C.
Abstract: Developing low-cost electrode materials with high performance is the priority among priorities for large-scale application of supercapacitors (SCs). Magadiite, the most ubiquitous material on Earth, is half-abandoned and half-forgotten, and it is extremely valuable for development to useful materials, such as 'a potential stock' to be developed. Herein, we conceive the transformation of magadiite to electrode materials, pursuing the aim 'waste can be turned into treasure'. Fortunately, three-dimensional honeycomb-like cobalt–nickel silicate (Cox Ni2-x SiO4 ) as high-performance electrode material for SCs is achieved via two simple steps of exfoliation and hydrothermal process. The bimetallic synergistic effect derived from Co/Ni can improve the reactivity of the material, and the honeycomb-like morphology can facilitate ion migration, so the electrochemical properties are enhanced. As a consequence, the Cox Ni2-x SiO4 electrode exhibited a specific capacitance of 1, 097 F/g (548 C/g) at 0.5 A/g, as well as excellent cyclic stability of 101% retention after 10, 000 cycles. The hybrid SC device is assembled by Cox Ni2-x SiO4 and active carbon (Cox Ni2-x SiO4 //AC), and it delivers an excellent energy density of 15.5 Wh/m 2  at a power density of 1.34 W/m 2 and cycling stability (100% after 10, 000 cycles). This work not only realizes the transformation of magadiite to transition metal silicates (TMSs) as electrode materials for high-performance SCs but also broadens the application of magadiite and opens up a novel strategy for synthesizing TMSs. Graphical abstract: Image 1 Highlights: Magadiite is converted to 3D honeycomb-like Cox Ni2-x SiO4 by a simple strategy. 3D honeycomb-like architecture facilitates the ionic diffusion. The bimetallic synergistic effect improves the electrochemical properties. Cox Ni2-x SiO4 exhibits a high capacitance of 1097 F/g at 0.5 A/g. Cox Ni2-x SiO4 //AC HSC device delivers excellent electrochemical performances.